2019
DOI: 10.1021/acsomega.9b00845
|View full text |Cite
|
Sign up to set email alerts
|

Star-Shaped ESIPT-Active Mechanoresponsive Luminescent AIEgen and Its On–Off–On Emissive Response to Cu2+/S2–

Abstract: Design and development of multifunctional materials have drawn incredible attraction in recent years. Herein, we report the design and construction of versatile star-shaped intramolecular charge transfer (ICT)-coupled excited-state intramolecular proton transfer (ESIPT)-active mechanoresponsive and aggregation-induced emissive (AIE) luminogen triaminoguanidine-diethylaminophenol ( LH 3 ) conjugate from simple precursors triaminoguanidine hydrochloride and 4-( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 90 publications
0
26
0
Order By: Relevance
“…From Figure D, it can be inferred that with the increasing glycerol fraction, more specifically with the increasing viscosity, there occurs fluorescence enhancement, owing to the suppression of the intramolecular rotation, followed by facile ESIPT, making the molecule highly emissive. Thus, the analyses further validate the AIE-induced fluorescence enhancement by the RIR mechanism. , Interestingly, in Figure S14, SI, it can be observed that with the increasing concentration of NAP-1 at room temperature from 0.1 to 100 μM, the intensity of the keto emission band is increased with a gradual decrease of the enol emission band. This speculates that in the excited state a facile proton transfer process takes place with the increasing concentration or aggregation of the compound, thereby facilitating the AIE-induced emission through RIR .…”
Section: Results and Discussionmentioning
confidence: 52%
“…From Figure D, it can be inferred that with the increasing glycerol fraction, more specifically with the increasing viscosity, there occurs fluorescence enhancement, owing to the suppression of the intramolecular rotation, followed by facile ESIPT, making the molecule highly emissive. Thus, the analyses further validate the AIE-induced fluorescence enhancement by the RIR mechanism. , Interestingly, in Figure S14, SI, it can be observed that with the increasing concentration of NAP-1 at room temperature from 0.1 to 100 μM, the intensity of the keto emission band is increased with a gradual decrease of the enol emission band. This speculates that in the excited state a facile proton transfer process takes place with the increasing concentration or aggregation of the compound, thereby facilitating the AIE-induced emission through RIR .…”
Section: Results and Discussionmentioning
confidence: 52%
“…Therefore, almost all the reported ESIPT‐based AIEgens for detection of metal cations involve SSB or SAA scaffolds, or at least, involve Schiff base or azine bearing an intramolecular hydrogen bond O─H···N. [ 28–57 ]…”
Section: Applicationsmentioning
confidence: 99%
“…The development of ESIPT‐based AIEgens has attracted great attention in the fields of physics, chemistry, and biology science. A growing number of ESIPT‐based AIEgens have been developed and applied in the detection of cations, [ 28–57 ] anions, [ 34, 35, 41, 43, 58–68 ] and small molecules, [ 69–76 ] bioimaging in the living cell and in vivo, [ 77–116 ] drug delivery systems (DDS), [ 44, 117–119 ] liquid crystal, [ 120–122 ] white light emitters, [ 123–127 ] and latent fingerprinting. [ 56, 128–131 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these compounds display keto-enol tautomerism, and both the nitrogen atom and oxygen atom in the Schiff bases can act as ligand donors for Cu 2+ and consequently produce stable coordination complexes via coordination effects. 40,41 The phenol group in phenol-based Schiff base units is deprotonated in the coordination process, which could diminish the electrondonating ability of the oxygen atom. [42][43][44][45][46] Moreover, it has been reported that the uorescence signal of hemicyanine-based NIR uorophores could be turned in a controllable manner by diminishing the electron-donating ability of the oxygen atom in its phenol group.…”
Section: Introductionmentioning
confidence: 99%